Development of Ag/ZnO/FTO thin film memristor using aqueous chemical route. (December 2015) - Dongale, Tukaram D.; Khot, Kishorkumar V.; Mali, Sawanta S.; Patil, Pramod S.; Gaikwad, Pawan K.; Kamat, Rajanish K.; Bhosale, Popatrao N.
Abstract: The present paper report the development of the Ag/ZnO/FTO memristor device using a simple aqueous chemical route. The structural, electrical, morphological and optical properties of Ag/ZnO/FTO memristor device are characterized using X-Ray diffraction (XRD), semiconductor characterization unit, field emission scanning electron microscopy (FESEM), and UV-Vis-NIR spectrophotometer respectively. The fabricated memristor device shows bipolar resistive switching behavior within low operating voltage (±0.88 V). The hysteresis loop in the I – V plane is the fingerprint characteristics of memristor and same has been seen in developed device. Furthermore, the effect of temperature on ZnO based memristor device is investigated using the thermal reaction model. The results suggested that, temperature of conductive filaments increases rapidly and affected the memory window of memristor.